Application of dijkstra algorithm to optimize waste transportation distribution routes in Tegal Regency - Santoso, Bayu Aji; Surur, Misbahu; Syefudin, Syefudin; Gunawan, Gunawan (Institute of Computer Science (IOCS), 2024)
Efficient waste management is essential for sustainable urban development, especially in densely populated areas such as Tegal Regency. The study addresses inefficiencies in current waste hauling routes that contribute to increased operational costs and environmental impacts due to long transit times and increased emissions. By applying the Dijkstra Algorithm, this study aims to optimize waste transportation routes to reduce these inefficiencies. This approach involves collecting primary and secondary data on the waste management system in Tegal, which is then analyzed using the dijkstra algorithm to determine the most efficient transport route. The findings show that route optimization can significantly reduce operational costs and carbon emissions, contributing to more sustainable waste management practices in the Tegal District. This study not only improves theoretical understanding of route optimization but also provides practical solutions to real problems in waste management systems.